2020
DOI: 10.1021/acs.jpclett.0c00333
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Core Level Photoelectron Spectra of Amino Acids Using Density Functional Theory

Abstract: Core level photoelectron spectroscopy is a widely used technique to study amino acids. Interpretation of the individual contributions from functional groups and their local chemical environments to overall spectra requires both high-resolution reference spectra and theoretical insights, for example from density functional theory calculations. This is a particular challenge for crystalline amino acids due to the lack of experimental data and the limitation of previous calculations to gas phase molecules. Here, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(37 citation statements)
references
References 68 publications
3
34
0
Order By: Relevance
“…It should also be noted that the use of the double hybrid functional xD-PBE0 brings no improvement relative to the regular hybrids. The better performance of hybrid functionals for K-shell XPS energies was also reported in the literature [112], while other studies found a better performance of regular GGAs [113]. However, many test sets used to judge the performance of binding energy calculations include only molecules with more moderate shifts [24,63,112,113].…”
Section: The Choice Of the Exchange Correlation Functionalmentioning
confidence: 74%
See 1 more Smart Citation
“…It should also be noted that the use of the double hybrid functional xD-PBE0 brings no improvement relative to the regular hybrids. The better performance of hybrid functionals for K-shell XPS energies was also reported in the literature [112], while other studies found a better performance of regular GGAs [113]. However, many test sets used to judge the performance of binding energy calculations include only molecules with more moderate shifts [24,63,112,113].…”
Section: The Choice Of the Exchange Correlation Functionalmentioning
confidence: 74%
“…Nevertheless, approximate core-hole simulation methods remain essential workhorses for highly complex spectroscopy simulations with applications ranging from in-operando electrocatalysis [124] to ultrafast dynamics [125] and pump-probe spectroscopy [126]. The efficiency of these methods enables the creation of high-volume data [112,127,128] which can be used for machine-learning-assisted spectral assignment [129][130][131]. The here presented ΔSCF and ΔIP-TP approaches as implemented in CASTEP are versatile and reliable for organic molecules in different environments and represent important tools in this context.…”
Section: Conclusion and Future Outlookmentioning
confidence: 99%
“…Following geometry optimisation and BE calculations, the two conformers of each amino acid with the most distinct BEs were retained for further investigation. For Ala, only the lowest energy conformer used in reference [3] was considered. The structures of each conformer are presented in the supplementary information (https://stacks.iop.org/EST/2/044005/mmedia).…”
Section: Theoretical Approachmentioning
confidence: 99%
“…Here, we expand and improve our previous approach to amino acids with aromatic side chains, including phenylalanine (Phe), tyrosine (Tyr), tryptophan (Trp), and histidine (His). Figure 1 shows a schematic of their atomic structures, including alanine (Ala) which is used as a reference throughout and which we have reported previously [3]. As for XPS studies on amino acids in general, very few studies exist on the aromatic subgroup.…”
Section: Introductionmentioning
confidence: 99%
“…This model at various levels of theory have been implemented in studying the core level shifts in aqueous glycine. 36,50,51 The calculated spectra, based on binding energies summarized in Table 2, are convoluted with a Gaussian with FWHM = 1.2 eV to resemble experimental spectra and are shown in Fig. 3.…”
Section: Resultsmentioning
confidence: 99%